Inserción de recursos digitales como apoyo didáctico para potenciar el proceso de enseñanza-aprendizaje de la asignatura de estudios sociales, unidad 3 y 4, en los niños del cuarto grado de educación general básica de la unidad educativa Adolfo Valarezo de la ciudad de Loja, período 2016 -2017. - Mora Robles, Yessenia Lisseth (2018)
The present research work arises due to certain learning difficulties presented by students, the main causes are lack of interest and attention, which is why this research was proposed that consisted of inserting digital resources as didactic support to enhance the teaching-learning process Of the subject of Social Studies, Unit 3 and 4, in the children of the fourth grade of basic general education of the Educational Unit "Adolfo Valarezo" of the city of Loja, period 2016 -2017. A fieldwork was carried out, which resulted in a diagnosis of the needs of students in the fourth grade of general basic education through revision of class plans, interview and observation of classes and together with the teacher a proposal was developed and implemented for Integrate ICT as a didactic resource for the teaching of the above mentioned students. Once the research was carried out, it was determined that the strategy implemented that included the use of educational software as didactic resource contributed to the students being more participatory, to the dynamism of the teaching process and to the achievement of the expected results.